Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/317
|View full text |Cite
|
Sign up to set email alerts
|

FAITH: Few-Shot Graph Classification with Hierarchical Task Graphs

Abstract: Speech Emotion Recognition (SER) has become a growing focus of research in human-computer interaction. An essential challenge in SER is to extract common attributes from different speakers or languages, especially when a specific source corpus has to be trained to recognize the unknown data coming from another speech corpus. To address this challenge, a Capsule Network (CapsNet) and Transfer Learning based Mixed Task Net (CTL-MTNet) are proposed to deal with both the single-corpus and cross-corpus SER tasks si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…(3) COX2 [35] is a dataset of molecular structures including 467 cyclooxygenase-2 inhibitors. (4) ENZYMES [46] is a dataset of 600 enzymes collected from the BRENDA enzyme database. ( 5) BZR [35] is a collection of 405 ligands for benzodiazepine receptor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) COX2 [35] is a dataset of molecular structures including 467 cyclooxygenase-2 inhibitors. (4) ENZYMES [46] is a dataset of 600 enzymes collected from the BRENDA enzyme database. ( 5) BZR [35] is a collection of 405 ligands for benzodiazepine receptor.…”
Section: Methodsmentioning
confidence: 99%
“…(4) ENZYMES [46] is a dataset of 600 enzymes collected from the BRENDA enzyme database. These enzymes are labeled into 6 categories according to their top-level EC enzyme.…”
Section: B Further Descriptions Of Datasetsmentioning
confidence: 99%
“…In other experiments, for the sake of simplicity and generality, we deploy GCN as the encoder for all the baselines and our proposed framework. [11,35,44], more recently, many studies [7,45,57] have shown that the performance of GNNs will severely degrade when the number of labeled node is limited, i.e., the few-shot node classification problem. Inspired by how humans transfer previously learned knowledge to new tasks, researchers propose to adopt the meta-learning paradigm [9] to deal with this label shortage issue [43].…”
Section: Choice Of Encodermentioning
confidence: 99%
“…MetaTNE [22] and RALE [24] also use episodic metalearning to enhance the adaptability of the learned GNN encoder and achieve similar results. However, those existing works usually directly apply meta-learning to graphs [41], ignoring the crucial distinction from images that nodes in a graph are not i.i.d. data, thus leading to several drawbacks as discussed in the paper.…”
Section: Choice Of Encodermentioning
confidence: 99%
“…Recently, many few-shot learning frameworks [15,45,53,56] have been proposed to deal with new tasks with limited samples. Typically, the main idea is to learn meta-knowledge from base classes with abundant samples (e.g., photo classes such as portraits).…”
Section: Introductionmentioning
confidence: 99%